ศึกษาปริทัศน์ : กรวยแห่งการเรียนรู้ - ศรีนนท์, มนัสวี (วารสาร ศึกษาศาสตร์ มมร; Vol 3 No 1 (2015): วารสารศึกษาศาสตร์ มมร ปีที่ 3 ฉบับที่ 1 (มกราคม-มิถุนายน 2558), 2018)
บทความเรื่องนี้สรุปได้ว่า การเรียนการสอนแบบ Active Learning มีความจำเป็นและควรต่อการจัดการเรียนการสอนเป็นอย่างยิ่ง เพราะกระบวนการเรียนรู้แบบ Active Learning เป็นกระบวนการที่ผู้เรียนได้เรียนรู้ผ่านการปฏิบัติจนส่งผลให้ผู้เรียนมีทักษะและจดจำได้แม่นยำ ดังนั้น กรวยแห่งการเรียนรู้จึงเป็นรูปแบบการเรียนรู้ผ่านการทำกิจกรรมระหว่างการเรียนการสอนในห้องเรียน โดยผู้สอนสามารถตั้งคำถามและผู้เรียนตอบคำถามได้เลย และผู้สอนสามารถดูผลการตอบคำถามของผู้เรียนได้ทันที ผู้เรียนก็มีความตื่นเต้นกับผลลัพธ์ในงานของตนด้วย Abstract This article concludes that Active learning is essential of learning process that students learn how to be an active learner. Active Learning can practice through the process of training thus students will receive skills and remembering. Therefore, we can call it, a cone of learning, which is one kind of learning approach while doing activities in the classroom. Furthermore, teacher can use asking and answer technique; in addition, the teacher can measure students’ comprehension immediately. Moreover, students were also excited with the results of their performances.